METHODS OF CERVICAL EXAMINATION IN PREGNANT WOMEN - I. S. Sidorova; D. A. Atabieva (Акушерство, гинекология и репродукция, 2016)
This article evaluates the validity of different diagnostic methods that are used when cervical pathology is suspected in pregnancy. Pregnant women were divided in two groups, one with pathological conditions of the cervix and the other lacking thereof. We used instrumental, cytological and bacteriological examination methods. Colposcopy provides the most important diagnostic criteria which allow early detection of cervical pathology.